China's automotive industry: structural impediments to socio-economic rebalancing. (2015) - Lüthje, Boy; Tian, Miao
The paper examines the development of the Chinese automobile industry in the context of the rebalancing of China's economy towards domestically-oriented growth, increased consumption and industrial upgrading. The authors analyse the regimes of accumulation, modes of regulation, and regimes of production in the car industry in China, and assess the geographic expansion of automobile manufacturing into new greenfield sites in recent years. In the face of the rising economic, social and environmental costs of the present mode of growth, strategic approaches are discussed to integrate innovation, industrial upgrading and reform of labour relations.